2020
DOI: 10.21203/rs.3.rs-17584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Men and loneliness in the ‘west’: A critical interpretive synthesis

Abstract: BackgroundLoneliness has received considerable attention in recent years, but has seldom been investigated through a gendered lens. This review aims to critically summarise research substantively related to men and loneliness.MethodA critical interpretive synthesis, incorporating a pre-defined search strategy, was employed to analyse a broad variety of data. The searches were conducted in July 2019, across seven databases: MEDLINE; PsycINFO; Scopus, ASSIA, SSCI; Sociological Abstracts; and Social Policy and Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The aim of the searches was to identify interventions to address loneliness in 14-24-year olds that also related to anxiety or depression: for example because the intervention targeted participants already experiencing depressive symptoms or diagnosed with depression, or because the measured outcomes included anxiety or depression as well as loneliness. We began with an 'a priori' search strategy focusing on interventions to address loneliness in young people that either also measured anxiety and/or depression (to identify prevention strategies and their mechanisms) or for which the sample comprised young people experiencing anxiety and/or depression (to identify treatment strategies and their mechanisms) [25]. Studies conducted outside of the UK were included as long as they were reported in English.…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the searches was to identify interventions to address loneliness in 14-24-year olds that also related to anxiety or depression: for example because the intervention targeted participants already experiencing depressive symptoms or diagnosed with depression, or because the measured outcomes included anxiety or depression as well as loneliness. We began with an 'a priori' search strategy focusing on interventions to address loneliness in young people that either also measured anxiety and/or depression (to identify prevention strategies and their mechanisms) or for which the sample comprised young people experiencing anxiety and/or depression (to identify treatment strategies and their mechanisms) [25]. Studies conducted outside of the UK were included as long as they were reported in English.…”
Section: Search Strategymentioning
confidence: 99%
“…Through CIS, the underlying data are transformed into 'synthetic constructs': higher-order theoretical concepts that capture diverse evidence [18,25,31]. These concepts summarise the key overarching themes in a diverse body of evidence, which may not be found in the literature being synthesised itself.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Social isolation and depression within older adults is expected to become the most prevalent cause of disease burden by 2030 [45] despite aging research establishing the importance of older adults remaining active in their communities [25] to deter some of these long-term effects [35]. However, older adults may struggle to seek help and build social networks due to emotional reticence [33] or actively disengaging with society [38].…”
Section: Older Adults and Online Civic Engagementmentioning
confidence: 99%
“…People typically do not openly discuss cybersecurity [41] which ultimately leads to lower awareness and can facilitate attacks [9] This is also typical of other difficult subjects (e.g. social isolation [33], privacy, etc.). This type of initiative has started to demonstrate how we can generate interest and engage communities in conversation and overall awareness of such topics.…”
Section: Spreading Cybersecurity Best Practice In the Communitymentioning
confidence: 99%